The New Virtual Crackdown on Sex Workers’ Rights: Perspectives from the United States - Peterson, Meghan; Robinson, Bella; Shih, Elena (Anti-Trafficking Review, 2019)
On 11 April 2018, the Fight Online Sex Trafficking Act (FOSTA) was signed into law in the United States. FOSTA introduced new provisions to amend the Communications Act of 1934 so that websites can be prosecuted if they engage ‘in the promotion or facilitation of prostitution’ or ‘facilitate traffickers in advertising the sale of unlawful sex acts with sex trafficking victims.’ While supporters of the law claim that its aim is to target human traffickers, its text makes no effort to differentiate between trafficking and consensual sex work and it functionally includes websites where workers advertise services or share information, including safety tips.[3] Following the law’s passage—and even before its full implementation—sex workers felt its impact as websites began to eliminate platforms previously used to advertise services. Backpage, an adult advertising website, was pre-emptively seized by the FBI. Other platforms began to censor or remove content related to sex work, including Google, Craigslist, and many online advertising networks. Sex workers in the United States have denounced the passage of FOSTA for reducing workers’ ability to screen clients and ensure safety practices. This paper provides an overview of the findings of a recent survey with sex workers in the United States, details the advent of similar initiatives in other countries, and explores how the legislation conflates trafficking with consensual sex work.